Effectiveness of Oral Health Education in Improving Oral Health Related Knowledge in Pregnant Mothers Attending the Ante-natal Clinic at the Divisional Hospital, Kotaligoda - R M ​ Jayasinghe; W N Kularatne; K K N D De Silva (Journal of Multidisciplinary Dental Research)
Objective of this study were to assess effectiveness of oral health education in improving oral health related knowledge in pregnant mothers attending ante-natal clinic. A questionnaire was used to assess oral health related knowledge before and following education programs. Post education answers were compared with previous ones. Minitab 18 was utilized for statistical analysis. Following education, knowledge on treatment options for teeth with infected pulp other than extraction, features of gingival diseases, association of diabetes mellitus and periodontal diseases and the change of oral health with ageing process was increased. More participants identified that oral hygiene maintenance is necessary for optimum periodontal health. The results indicated that mean post knowledge was significantly higher than mean pre knowledge (p< 0.001). There was a statistically significant association between pre knowledge and monthly income. Education programs significantly improve the knowledge on oral health of the pregnant mothers. However, the increase of knowledge does not vary according to the age, monthly income and education level of them. It is recommended that pregnant mothers should be educated regularly on oral health and oral health practices as the knowledge will be beneficial for long term oral health behavior. Keywords: Pregnant mother, Effectiveness, Oral health education